The effect of a proposed training program using small games to develop some elements of physical qualities (flexibility, speed, agility) among fifth-grade elementary school students. - hamadi, djamel; Yaakoubi, fateh (sports creativity, 2025)
Small-scale games in sports are of exceptional importance, offering a new approach to engaging with young people and building a solid foundation. They provide all the necessary resources to help children improve, develop their skills, and express their natural desires, inclinations, and needs. Furthermore, they offer the enjoyment gained through participation, whether physical, skill-based, psychological, or cognitive (intellectual). This should be done in a planned manner that ensures continuity throughout educational and training sessions, leading to positive progress in performance results. Therefore, it is essential to find the most effective methods and approaches to achieve the educational program objectives for this core subject within the school environment. Schools, with their large number of participants, are the place for preparing future generations, and the specific needs of this age group must be considered. Incorporating small-scale games can be a successful way to develop physical abilities in particular, while also adding fun and enjoyment to the lessons. Caring for childhood means caring for society as a whole, because children are the nation's wealth, its foundation, and its future. This stage is considered the best stage for learning because children at this age are characterized by calm movement and motor control during physical education and sports classes. To capitalize on this calm movement, a special program of small games must be provided, which works to develop the physical abilities of primary school students. Nawal Ibrahim Shaltout and Safaa Al-Kharboutli both believe that developing physical attributes equips children with the ability to handle the burdens of daily life and prepares them for future life. This development of physical elements and motor skills achieves children's physical growth as one of the elements of integrated development and contributes significantly to achieving the general goals of education, which is increased productivity. However, this element is not clearly stated in the objectives of primary education. The researcher believes that paying attention to the process of developing physical elements is of great importance, especially in childhood, as it works to raise the efficiency of the body’s functional organs and systems and integrate their performance through semi-sports-like motor activities that are appropriate to the child’s growth. The latter requires a qualified teacher in order to give the child a positive opportunity to acquire balanced physical fitness, from the lesson aimed at developing physical qualities (flexibility, speed, agility) in this age group.